Cultural Adaptation of a Shared Decision-Making Intervention to Address the Needs of First Nations, Métis and Inuit Women - Jull, Janet (Université d'Ottawa / University of Ottawa, 2014)
Background: Little is known about shared decision-making (SDM) interventions with Aboriginal Peoples. Purpose: To explore Aboriginal women’s SDM needs and engage Aboriginal women in culturally adapting an SDM approach. Methods: Three studies were guided by an advisory group, ethical framework and a postcolonial theoretical lens. 1. A systematic review of the literature to identify health decision-making interventions to support Indigenous Peoples. 2. An interpretive descriptive qualitative study using individual interviews with Aboriginal women to explore decision-making needs. 3. An interpretive descriptive qualitative study to culturally adapt and usability test the Ottawa Personal Decision Guide (OPDG) to support decision making by Aboriginal women. Results: 1. The only eligible intervention study was a randomized control trial conducted in the United States with 44 Indigenous students. Compared to baseline, post-intervention the students demonstrated increased knowledge and use of a four-step decision-making process. 2. Interviews with 13 Aboriginal women supported SDM. Shared decision-making needs were represented by four major themes and presented in a Medicine Wheel framework: To be an active participant; To feel safe with care; Engagement in the decision process; Personal beliefs and community values. Supports for each of the major themes focused on the relational nature of shared decision-making. 3. Aboriginal women participated in two focus groups (n=13) or usability interviews with decision coaching (n=6). For culturally adapting the OPDG seven themes were identified: “This paper makes it hard for me to show that I am capable of making decisions”; “I am responsible for my decisions”; “My past and current experiences affect the way I make decisions”; “People need to talk with people”; “I need to fully participate in making my decisions”; “I need to explore my decision in a meaningful way”; “I need respect for my traditional learning and communication style.” Conclusions: There is little evidence on SDM interventions with Indigenous Peoples. Although Aboriginal women support SDM, they may have unmet decision-making needs. The OPDG was culturally adapted to be combined with decision coaching and needs to be evaluated.